Management of a Multiple Endocrine Neoplasia 1 Patient in Pregnancy - Deepanshu Dhiman; Summit Dev Bloria; Pranshuta Sabharwal; Rashi Sarna; Rajeev Chauhan (Wolters Kluwer Medknow Publications, 2020)
Multiple endocrine neoplasia (MEN) syndrome has rarely been reported during pregnancy. The multiple manifestations of the syndrome along with the normal body changes associated with pregnancy can prove to be difficult to manage. We describe our experience of the diagnosis and management of MEN1 syndrome in a pregnant female.